Decent Work and Poverty Reduction Strategies - Hughes, Steve; Haworth, Nigel (Relations industrielles / Industrial Relations, 2011)
Using strategies first developed in the inter-war years, the ILO has repositioned itself to play a leading role in our understanding of the relationship between employment policies and growth, particularly in relation to poverty reduction strategies. To do this, the ILO has forged increasingly strong relationships with key international financial institutions (IFIs), in which the inclusion of ILO-driven strategies for Decent Work and core labour standards has been important. Whilst this repositioning has been questioned by some who fear that an original purpose of the 110 may be lost, and the technical implementation of the ILO agenda in conjunction with the IFIs is not without difficulties, the ILO's status as a major international agency for the advancement of human development has been reinforced.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic crisis; Employment policies; International; LABOR market; Labor Unions; POVERTY; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies